Enhancement of nutritional and textural properties of meat analogues using silkworm pupae powder via freeze alignment technique - Parinya Boonarsa; Kyuya Nakagawa; Kriangsak Banlue; Sirithon Siriamornpun (Food Chemistry: X)
The demand for sustainable, high-protein meat alternatives has driven interest in novel ingredients, yet the use of insects as the sole protein source remains underexplored. This study investigates silkworm pupae powder (SW) as a primary ingredient in meat analogues produced using the freeze alignment technique. SW was incorporated at 5, 10, and 15 g/100 g and compared to soy protein (SP). Increasing SW levels enhanced viscosity, pseudoplastic behavior, and gel-like properties but reduced water-holding capacity and total sulfhydryl content (p < 0.05). SW significantly increased protein content (4–55 g/100 g DW) while reducing carbohydrates (17–85 g/100 g DW). Textural analysis showed improved chewiness, cohesiveness, and firmness, with fiber-like structures forming at 5–10 % SW. SW-based analogues had a higher essential amino acid index (0.59–0.98) than SP (0.47). These findings highlight SW as a promising, nutrient-rich, and sustainable protein source for meat analogues, expanding possibilities for insect-based alternatives.